The Future Challenges of China-Lao Railway on Lao’s Economic and Social Development - Ermylina, Eva (Universitas Muhammadiyah Malang, 2023)
This paper tends to examine the impact and challenge of the China-Lao Railway that has been operating since December 2021 on Lao’s economic and social development. As a landlocked country, Lao has been facing difficulties in boosting its economic and human improvement due to the lack of infrastructure and development capacity. However, Lao is also geographically strategic because its position is in the middle of the Indo-China area. It makes Lao eagerly wants to be a land-linked country through the railway that connects China and other countries in the region. Under the project Belt and Road Initiative, Lao, for the first time, has a high-speed railway that links the capital city, Vientiane, and Boten, the China-Lao border, and further connects Kunming, the Chinese provincial capital. After one year of implementation, the positive impact has been felt by Laotians such as the tourism sectors, goods flow, and education sectors. However, land compensation and environmental issue are the negative impacts that Laotians encounter. Lao also might face some challenges to sustaining this railway’s benefits namely a debt trap, transnational crime, and severe corruption.